"If you compress the spring, it will snap back hard": The Ukrainian crisis and the balance of threat theory. (March 2015) - Bock, Andreas M; Henneberg, Ingo; Plank, Friedrich
The narrative of an aggressive and neo-imperialist Russia that has dominated analyses of the 2014 Ukrainian crisis lacks theoretical rigour. We argue that a sustainable transformation of the Ukrainian crisis requires an accurate analysis of the context of the conflict, which should include an understanding of Moscow's perception of the threats to its interests. This policy brief develops a theoretical understanding of the Ukrainian crisis through the lens of Stephen M. Walt's balance of threat theory. We conclude that a realist analysis will help to explain Russian actions.